(NnAUKOWO(B-(NPRAKTI^NIJ KOMENTAR kRIM)QÆNALXNOGO KODEKSU uKRAÇNI (B/s)E ((NkI)QÇW (B:s)E (NaT)QÆKA(B,s)E, 2005)
(NkOMENTAR DO kRIM)QÆNALXNOGO KODEKSU uKRAÇNIs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NpRAWOs -- (NkRIM)QÆNALXNE PRAWOs)E; (NKRIM)QÆNALXNIJ KODEKSs)E; (NNAUKOWO(B-(NPRAKTI^NIJ KOMENTARs; (NZAKONIs; (NZLO^INs; (NPOKARANNQs; (NSUDIM)QÆSTXs)E